Investigation of the effect of quercetin on experimental traumatic cardiac injury in rats - Taysi, Muhammed Enes; Demirel, Mustafa Enes; Cetinkaya, Ayhan; Saylan, Aslihan; Kayis, Seyit Ali; Alisik, Murat (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardioprotection is an important aspect of preventive medicine. Quercetin, a plant-derived flavonoid with antioxidant and anti-inflammatory properties, has been linked to reduced cardiovascular risk.ObjectiveTo investigate the cardioprotective effects of quercetin in rats with traumatic cardiac injury (TCI).MethodsFifty-two Wistar Albino rats were randomly divided into six groups: control (n = 7); TCI only (n = 9); TCI + DMSO (n = 6); and TCI + quercetin at 10, 20, or 40 mg/kg (n = 9 each). Quercetin or DMSO was given intraperitoneally at 0.5, 12, and 24 h after trauma. Cardiac trauma was induced by dropping a standardized weight on the chest. Serum biochemical parameters (GPx, SOD, IL-1, IL-33, sST2, MDA) were measured by ELISA, and histopathological damage was scored semiquantitatively. Data were analyzed using ANOVA or Kruskal–Wallis tests with p < 0.05 as significant.ResultsGPx elevation was detected only at 10 and 20 mg/kg (vs. TCI; p < 0.05); 40 mg/kg was non-significant (p > 0.05). Overall, IL-1 differed among groups (p = 0.008), with no pairwise comparisons significant after correction (all p > 0.05). For IL-33, an overall group effect was observed (p = 0.025), while adjusted pairwise tests did not show a consistent between-group pattern (p > 0.05). In contrast, malondialdehyde (MDA) levels were significantly reduced, particularly at the highest dose of 40 mg/kg (p < 0.05). Superoxide dismutase (SOD) and soluble suppression of tumorigenicity-2 (sST2) levels showed no significant differences among groups (p > 0.05). Histopathological evaluation demonstrated that quercetin mitigated myocardial degeneration, inflammatory infiltration, edema, vascular congestion, hemorrhage, and necrosis in a dose-dependent manner, with the most pronounced protective effects observed at 40 mg/kg (p < 0.05).ConclusionsQuercetin, especially at 40 mg/kg, may help prevent secondary cardiac injury after trauma by reducing oxidative stress and limiting histopathological damage. These results support quercetin's cardioprotective potential and warrant confirmation in larger preclinical models with broader designs.